Penegakan Hukum Dalam Melindungi Sumber Kekayaan Alam Laut Dan Akibat Hukumnya Menurut UNCLOS 1982 - Wahyuni Thovyan; Johanis Steny Franco Peilouw; Yanti Amelia Lewerissa (PATTIMURA Law Study Review, 2023)
Marine natural resources as stipulated in Articles 192 and 193 of UNCLOS 1982 make the community and may not do so. But there are still things to do, like one example of the case where baby lobsters were taken and explored in the Aru Islands area. the problem of the case that there were found two things, namely what are the arrangements regarding the obligations of the state and law enforcement in protecting marine natural resources, with the aim of knowing the two things that are the problem, which uses normative juridical methods with the Statute Approachh, Case Approachh, and Conceptual approaches Approach and using primary, secondary and tertiary legal materials. The results of this study indicate that, the regulation regarding state obligations is the fulfillment of the elements and responsibilities carried out. Then from law enforcement in protecting marine natural resources according to existing regulations and implemented according to applicable law, if applicable regulations are violated then there are sanctions for people who violate applicable regulations which have been regulated and given permission in the sale of buy the baby lobster if it comes in at the size specified by the permit then it can be exported out if otherwise it is not in accordance with the rules of the permit then anyone who violates it will be subject to criminal sanctions.